Mapping Meaning in Kanji: A Quasi-Experimental Study on Learning Gains Among Indonesian Learners of Japanese - Noviyanti Aneros; Herniwati; Dianni Risda; Melia Dewi Judiasri (Chi e Journal of Japanese Learning and Teaching, 2025)
Japanese language learners whose native writing systems do not include kanji often encounter difficulties in using kanji effectively in complex discourse, remembering onyomi and kunyomi readings, and understanding their meanings. This study explores the effectiveness of kanji mapping as a strategy to enhance kanji comprehension and memorization among second-year students in the Japanese language Education Program at Universitas Pendidikan Indonesia (UPI). The research focuses on the Chukyu Hyouki course, which covers 220 N3 level kanji from the Kanji Master N3 textbook. Using a quasi-experimental one-group pre-test and post-test design, the study was conducted over three sessions involving 23 fourth-semester students. Data were collected through pre-tests, post-tests, and questionnaires. The findings indicate a significant improvement in kanji mastery, with average test scores increasing from 66.6 to 88.1. Questionnaire responses further suggest that students found kani mapping helpful in organizing and internalizing onyomi, kunyomi, and bushu (radicals). This structured visual approach supported accurate contextual application and contributed to long-term retention. Overall, the results support the integration of kanji mapping into kanji instruction to improve learner outcomes.